Implementation of Green Ergonomics to Improve Work Environment Conditions by Using the Sustainable Work Index (SWI) in the Shoe Manufacturing Industry - Sukapto, Paulus; Geovando Gita, Graemmy; Amanda, Gabriela; Liauw, Justin; Gunawan, Maisie (Jurnal Improsci, 2025)
Background. The work system consists of people, equipment, and environments that are robustly integrated to achieve the goals of the work system. Aims. The purpose of this study is to evaluate and improve the conditions of the work environment with a Green Ergonomics approach using the Ergonomic Triad Model that focuses on the Sustainable Work Index (SWI). Method. The four SWI factors that were analyzed were Human Work Factor (HWF), Workstation Design Factor (WDF), Organizational Environment Factor (OEF), and Environmental Conditions Factor (ECF). Result. The results of the initial SWI calculation were in the Materials Inspection (68.45%) and Packing (63.83%) departments, categorized as "regular". Improvement efforts to enhance SWI values include adjusting working hours, providing ergonomic chairs, implementing visual displays that promote healthy habits, and improving working environment conditions, such as lighting and room temperature. Conclusion. This study demonstrates that a comprehensive Green ergonomics approach can enhance the quality of work and significantly improve worker welfare. Implementation. The implementation of improvements for these five things resulted in SWI values in the Material Inspection Department (to 82.40%) and in Packing (to 84.25%);